(untitled) (Archives of Clinical Psychiatry, 2005)
Dementia is a syndrome characterized by progressive impairment of cognitive functions, particularly in memory, which affects social and occupational activities. The differential diagnosis must, firstly, identify potentially treatable causes of cognitive impairment, addressing the different etiologies of reversible dementia such as metabolic alterations, intoxications, CNS infections, and nutritional deficiencies. The correct and early diagnosis of primary degenerative dementia carries therapeutic and prognostic implications, which may attenuate the inevitable cognitive and behavioral deficits. Definitive diagnoses of most primary dementia syndromes rely on post-mortem neuropathological examination. However, a thorough clinical evaluation, including a detailed clinical history, physical and neurological examination, combined with biochemical determinations and neuroimaging, provide a more accurate differential diagnosis. Technological innovations making use of both structural and functional neuroimaging methods, as well molecular biology and molecular genetic techniques, have presented in the recent literature a strong perspective for the early diagnosis of dementia, especially of Alzheimer disease. The different etiologies involved in the development of dementia syndromes, as well as the respective diagnostic conduct, will be reviewed in this article.